MONO+KM: Knowledge Management in Collaborative Project Development - González, Oscar (2016)
In the dynamics of collaborative project management, participating organizations make great efforts and provide technical, technological and human resources to achieve a product they can hardly develop individually.Although there are tools to integrate, monitor and manage processes for such projects, it is not uncommon to find technological support to manage the knowledge generated during their execution. Usually this knowledge is part of the experience of participants but it is not recovered or documented nor is it used an organizational level, thus losing an important asset.In this study, we propose a technique in which a knowledge management approach is applied to the management of collaborative projects and where knowledge is expressed in terms of decisions.This is achieved through the analysis of verbal interactions that occur among participants in these projects, the identification and recovery of decisions Grounded Theory Method (GTM) techniques, and the specification of a set of concrete usage scenarios.The technique was applied in MONO, a framework for integration, control and optimization of production processes in which digital content companies in the creative industry work collaboratively.The study provides an annotation model, which, without being intrusive, allows for the recovery and structuring of knowledge expressed as decisions, thus making possible its replication in other domains.